PENGARUH MOTIVASI, KOMUNIKASI, DAN DISIPLIN KERJA TERHADAP KEPUASAN PEGAWAI DINAS PERHUBUNGAN BALIKPAPAN - Wulan Syaharani; Misna Ariani; Imam Arrywibowo (Jurnal GeoEkonomi, 2024)
The purpose of this study was to determine the effect of Work Motivativon, Comunication, and Work Discipline on Job Satisfaction of empolyess at the Departement of Transportation Balikpapan. The sampling technique in this study was purposive sampling with a sample 60 employees from the Departement of Transportation in Balikpapan. Methods of data collection is done by distributing questionnaires. This study uses SmartPLS in processing data. The results of this study indicate that the motivation variable has a significant effect on job stratification of employees at the Departement of Ttransportation in Balikpapan. Communication variable has no significant effect on job stratification of employees at the Departement of Ttransportation in Balikpapan. Work Dicipline variable has no significant effect on job stratification of employees at the Departement of Ttransportation in Balikpapan.